Preparation method of seaweed derived alloy carbon sodium ion battery negative electrode material
Through the preparation of seaweed-derived alloy carbon material, the problems of volume expansion and active substance peeling during the charge and discharge cycle of sodium ion battery negative electrode material are solved, the high electrochemical performance and cycle stability of the material are achieved, and the service life of the battery is extended.
Patent Information
- Application Number
- CN202311105964.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-18
AI Technical Summary
The existing sodium ion battery negative electrode materials have problems such as rapid volume expansion and active substance peeling during the charge and discharge cycle, resulting in rapid attenuation of capacity and hindering the research progress of alloy negative electrode materials in sodium ion batteries.
Seaweed-derived alloy carbon material is used as the negative electrode material. By carbonizing seaweed leaves and reacting with metal salts under microwave, a unique rough and porous structure is formed, which alleviates the volume changes of the alloy material during sodiumization/desodiumization and improves the stability and electrochemical properties of the material.
It significantly improves the electrochemical performance and cyclic stability of the negative electrode material of sodium ion battery, reduces electrode powdering and active material peeling caused by volume changes, and extends the service life of the battery.
Smart Images

Figure CN119634739A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a method for preparing a seaweed-derived alloy carbon sodium ion battery negative electrode material. Background Art
[0002] Lithium-ion batteries have become a major energy storage device due to their high energy density and excellent cycle stability, and are widely used to store energy collected from renewable energy sources such as solar, wind, and hydroelectric power. Nevertheless, the scarcity of lithium metal and its safety issues have led to an urgent need to find alternatives to lithium-ion batteries. In this context, sodium-ion batteries have been widely studied due to their abundant reserves of sodium and their similar working mechanism to lithium-ion batteries. However, compared with Li In comparison, Na The large ionic radius of the anode material prevents the embedding of sodium ions into the anode material. It is urgent to develop anode materials with high electrochemical performance, high conductivity and excellent cycle stability. Therefore, it is crucial to improve the ion / electron transfer rate of the anode material and increase the number of active sites for sodium storage.
[0003] Carbon-based materials are regarded as one of the most promising anode materials due to their considerable ion storage capacity, good electrical conductivity and excellent thermal / chemical stability. Recently, seaweed-derived carbon has attracted extensive attention as a hard carbon anode material due to its many advantages, including abundant raw materials, low cost, sustainability and economic benefits. Alloy-type anode materials can alloy with metallic Na to obtain high theoretical specific capacity (300-2000mAh / g) and low sodium potential (less than 1.0V (vs. Na / Na)). + )) shows great potential in sodium-ion battery applications. However, alloy-type negative electrode materials have the problem of rapid volume expansion, which leads to electrode pulverization and the peeling of active materials from the current collector, resulting in rapid capacity decay during the charge and discharge cycle, which seriously hinders the research progress of alloy-type negative electrode materials in sodium-ion batteries. Summary of the invention
[0004] In order to solve the problems existing in the prior art, the present invention provides a method for preparing a seaweed-derived alloy carbon sodium ion battery negative electrode material, which uses seaweed, which is rich in resources and low in cost, to achieve a unique rough and porous structure through carbonization, which is conducive to alleviating the volume change of the alloy material during the sodiumization / de-sodiumization process, improves the stability of the material, and significantly improves the electrochemical performance of the alloy material. In addition, the seaweed-derived alloy carbon is prepared using a one-step microwave method, and the preparation process is solvent-free throughout, the preparation method is simple, the time is short, and the yield is high.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A method for preparing a seaweed-derived alloy carbon sodium ion battery negative electrode material comprises the following steps:
[0007] Step 1, drying the cleaned seaweed leaves;
[0008] Step 2, chopping the dried seaweed leaves and calcining and carbonizing them together with an activator;
[0009] Step 3, washing the carbonized material with deionized water until it is neutral, and drying it to obtain a seaweed precursor;
[0010] Step 4: Grind the seaweed precursor and the two metal salts evenly, and react them under microwave radiation to obtain the seaweed-derived alloy carbon sodium ion battery negative electrode material.
[0011] Furthermore, in step 4, the two metal salts are one or a combination of acetate and nitrate, and the metal elements in the metal salt include any two of Sb, Bi, Sn, Pb, Co, Al, Mn, Fe, Co, Ni, Cu, Zn, and In.
[0012] Furthermore, in step 4, the mass ratio of the seaweed precursor to the two metal salts is (1-3): (1-3):
[0013] (1-3).
[0014] Furthermore, in step 4, the microwave reaction time is 30s-5min, and the power is 500w-2000w.
[0015] Furthermore, in step 2, the carbonization process is: under an inert atmosphere, the heating rate is 1-5°C / min, the carbonization temperature is 300°C-1000°C, and the insulation time is 2-6h; after the insulation time is reached, it is naturally cooled to room temperature.
[0016] Furthermore, in step 2, the activator includes at least one of sodium hydroxide and potassium hydroxide.
[0017] Furthermore, in step 2, the mass ratio of the dried seaweed leaves to the activator is (1-4):(4-1).
[0018] Furthermore, the inert atmosphere includes a combination of one or more of helium, neon, argon, krypton, xenon, radon and nitrogen.
[0019] Furthermore, in step 2, the length of the chopped seaweed leaves is less than 0.5 mm.
[0020] Furthermore, in step 1, the seaweed blade is the blade portion remaining after the central rib of the seaweed is removed.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention provides a method for preparing a seaweed-derived alloy carbon negative electrode material for a sodium ion battery. A hard carbon precursor is prepared from seaweed, and the precursor is composited with an alloy material to form a seaweed-derived alloy carbon material as a negative electrode material for a sodium ion battery. From an environmental protection perspective, the use of seaweed to synthesize electrode materials will significantly reduce the negative impact on the environment. The carbon derived from seaweed-derived alloy carbon exhibits good electrochemical properties, which is mainly attributed to the fact that the seaweed-derived alloy carbon inherits the unique natural morphology, structure and properties of seaweed to a certain extent. During the carbonization process, huge micropores and mesopores are formed on the surface of the seaweed-derived alloy carbon, which can effectively reduce the volume change of the alloy material, prevent the formation of dendrites during electroplating and peeling, and improve the electrochemical stability. The formation of the alloy provides abundant active sites for redox reactions, which can absorb more Na + , providing high specific capacity. In addition, compared with single metals, bimetallic alloys can improve the overall electrochemical performance by synergistically acting as a buffer substrate to improve the stability of the material; among them, bimetallic alloys include Co-Sb alloys, Fe-Sb alloys, Sn-Co alloys, In-Sb alloys, Ni-Sb alloys, Sn-Sb alloys, Sb-Bi alloys, Si-Bi alloys, etc. For example, due to the high cycle stability of Sb and the high sodium ion storage capacity of Sn, SnSb alloys react with Na ions to form Na3Sb and Na 3.75 The theoretical maximum storage capacity of Sn can reach 752 mAh / g. The smaller particle size and porous structure of SnSb alloy can serve as a buffer space to accommodate the volume change of Sb and prevent the electrode from collapsing during the cycle. This nanoporous structure shortens the Na + The diffusion distance is shortened, thereby enhancing the reaction kinetics, while providing a larger surface area, resulting in efficient electrolyte penetration and interfacial reactions. Sb and Bi elements belong to the same main group (VA) and have the same atomic arrangement, which determines that they can be mixed in any molar ratio. The existence of the two phases in the BiSb alloy can act as a mutual buffer for each other, thereby offsetting the volume change caused by sodium insertion / extraction, thereby ensuring structural integrity, improving cycle stability, and ensuring high capacity.
[0023] The method for preparing the seaweed-derived alloy carbon sodium ion battery negative electrode material of the present invention comprises mixing the carbonized seaweed with two metal salts at room temperature. Under the rapid action of microwave radiation, the metal ions are rapidly reduced to nanoparticles to form an alloy, and react with the carbon of the seaweed precursor to form a strong metal support interaction, thereby improving the structural stability. The seaweed-derived alloy carbon also produces more active sites to store sodium ions, increasing the sodium ion diffusion rate, thereby improving the electrochemical performance. In addition, the synthesis process is very fast, solvent-free, and has a high yield. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a SEM image of the seaweed-derived alloy carbon material obtained in Example 1;
[0025] Figure 2 is the cycle performance curve of the seaweed-derived alloy carbon material obtained in Example 1 as a negative electrode material for a sodium ion battery at a current density of 100 mA / g;
[0026] Figure 3 This is an EIS test curve of the seaweed-derived alloy carbon material obtained in Example 1 as a negative electrode material for a sodium ion battery. DETAILED DESCRIPTION
[0027] The technical solution of the present invention will be clearly and completely described below in conjunction with the drawings and embodiments. Obviously, the described embodiments are only part of the embodiments of the invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0028] A method for preparing a seaweed-derived alloy carbon sodium ion battery negative electrode material comprises the following steps:
[0029] Step S1, repeatedly washing the seaweed leaves with deionized water to remove dirt and soluble impurities, and then drying them in a drying oven;
[0030] Wherein, the natural seaweed-derived alloy carbon raw material is the blade or leaf part of the seaweed left by separating the main trunk of the initially collected seaweed;
[0031] Step S2, chopping the dried material obtained in step S1, mixing it with the activator in proportion, and putting it into a crucible, and calcining and carbonizing it in a tube furnace. The carbonization process is: under an inert atmosphere, the heating rate is 1-5°C / min, the carbonization temperature is 300°C-1000°C, the holding time is 2-6h, and it is naturally cooled to room temperature after the holding time is reached;
[0032] The length of the chopped leaves of the dried material obtained is less than 0.5 mm.
[0033] Step S3, washing the material obtained by carbonization in step S2 thoroughly with deionized water to a neutral pH, and drying to obtain a seaweed precursor;
[0034] Step S4, weighing the seaweed precursor and the two metal salts according to a proportion, grinding them evenly, and reacting them in a household microwave oven to obtain the final product.
[0035] Furthermore, in step S2, the activator includes at least one of potassium hydroxide and sodium hydroxide.
[0036] Furthermore, in step S2, the mass ratio of the dried material to the activator is (1:4)-(4:1).
[0037] Further, in step S2, the inert atmosphere includes a combination of one or more of helium, neon, argon, krypton, xenon, radon and nitrogen.
[0038] Furthermore, in step S2, the carbonization temperature can be 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C or 1000°C, or other temperature values within this range; the heating rate can be 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min, or other values within this range; the holding time can be 2h, 3h, 4h, 5h or 6h, or other values within this range.
[0039] Furthermore, in step S4, the mass ratio of the seaweed precursor to the two metal salts is (1-3): (1-3): (1-3).
[0040] Furthermore, in step S4, the two metal salts include a combination of one or more of acetate and nitrate, and the metal elements in the metal salts are any two of Sb, Bi, Sn, Pb, Co, Al, Mn, Fe, Co, Ni, Cu, Zn, and In.
[0041] Furthermore, in step S4, the microwave reaction time is 30s-5min, and the microwave oven power is 500w-2000w.
[0042] The preparation method of the seaweed-derived alloy carbon sodium ion battery negative electrode of the present invention is described in detail below through specific examples.
[0043] Example 1
[0044] A method for preparing a seaweed-derived alloy carbon sodium ion battery negative electrode material comprises the following steps:
[0045] Step S1, repeatedly washing the seaweed leaves with deionized water to remove dirt and soluble impurities, and then drying them in a drying oven;
[0046] Step S2, cutting the dried material obtained in step S1 into a length less than 0.5 mm, and putting it into a crucible with potassium hydroxide in a ratio of 3:1, and calcining and carbonizing it in a tube furnace. The carbonization process is: in a nitrogen atmosphere, the heating rate is 3°C / min, the carbonization temperature is 500°C, and the holding time is 4h; after the holding time is reached, it is naturally cooled to room temperature;
[0047] Step S3, washing the carbonized material thoroughly with deionized water to a neutral pH, and drying to obtain a seaweed precursor;
[0048] Step S4, weighing the seaweed precursor, antimony acetate and bismuth nitrate in a ratio of 2:1:1, grinding them evenly, and putting them into a household microwave oven at room temperature, controlling the reaction power to 700w, and the reaction time to 2min to obtain the final product.
[0049] See also Figure 1 , is the SEM image of the seaweed-derived alloy carbon material obtained in Example 1, Figure 1 It can be seen that huge micropores and mesopores are formed on the surface of the seaweed-derived alloy carbon material prepared in Example 1. The presence of such pores and cavities is conducive to improving the charge storage capacity of the carbon material, providing sufficient electrochemical reaction active sites to react with sodium ions, thereby improving the electrochemical performance.
[0050] The seaweed-derived alloy carbon material, acetylene black and SBR prepared in Example 1 were mixed and ground in a ratio of 7:2:1, and then an appropriate amount of deionized water was added to fully grind to form a uniform slurry. The slurry was coated on the copper foil surface, and after drying, the electrode was punched to prepare the electrode, and the sodium sheet was used as the counter electrode to assemble the button battery.
[0051] See also Figure 2 , is the cycle performance curve of the seaweed-derived alloy carbon material obtained in Example 1 as a negative electrode material for a sodium ion battery at a current density of 100 mA / g. Figure 2 It can be seen that after 100 cycles, the specific capacity of the carbon material obtained by rapid cooling is 253.1 mAh / g.
[0052] See also Figure 3 , is a graph of the electrochemical impedance spectroscopy (EIS) test of the seaweed-derived alloy carbon material obtained in Example 1 as a negative electrode material for a sodium ion battery in a frequency range of 100kHz to 10mHz. Figure 3 It can be seen that the prepared hard carbon material has a lower charge transfer resistance, indicating a higher conductivity of the electrode, which is attributed to the dealloying process of metallic Sb, (Na3Sb→Sb+3Na + +3e - ) at about 0.8V (vs.Na / Na + ) can be completed in almost one step. The introduction of Sb atoms into Bi can improve the kinetics of metallic Bi through a multi-step sodium removal process (Na3Bi→NaBi+2Na + +2e - , NaBi→Bi+Na + +e - ).
[0053] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a seaweed-derived alloy carbon sodium ion battery negative electrode material, characterized in that: The following steps are involved: Step 1, drying the cleaned seaweed leaves; Step 2, chopping the dried seaweed leaves and calcining and carbonizing them together with an activator; Step 3, washing the carbonized material with deionized water until it is neutral, and drying it to obtain a seaweed precursor; Step 4: Grind the seaweed precursor and the two metal salts evenly, and react them under microwave radiation to obtain the seaweed-derived alloy carbon sodium ion battery negative electrode material.
2. The method for preparing a seaweed-derived alloy carbon sodium ion battery negative electrode material according to claim 1, characterized in that: In step 4, the two metal salts are one or a combination of acetate and nitrate, and the metal elements in the metal salt include any two of Sb, Bi, Sn, Pb, Co, Al, Mn, Fe, Co, Ni, Cu, Zn, and In.
3. The method for preparing a seaweed-derived alloy carbon sodium ion battery negative electrode material according to claim 1, characterized in that: In step 4, the mass ratio of the seaweed precursor to the two metal salts is (1-3): (1-3): (1-3).
4. The method for preparing a seaweed-derived alloy carbon sodium ion battery negative electrode material according to claim 1, characterized in that: In step 4, the microwave reaction time is 30s-5min, and the power is 500w-2000w.
5. The method for preparing a seaweed-derived alloy carbon sodium ion battery negative electrode material according to claim 1, characterized in that: In step 2, the carbonization process is: under an inert atmosphere, the heating rate is 1-5°C / min, the carbonization temperature is 300°C-1000°C, and the insulation time is 2-6h; after the insulation time is reached, it is naturally cooled to room temperature.
6. The method for preparing a seaweed-derived alloy carbon sodium ion battery negative electrode material according to claim 1, characterized in that: In step 2, the activator includes at least one of sodium hydroxide and potassium hydroxide.
7. The method for preparing a seaweed-derived alloy carbon sodium ion battery negative electrode material according to claim 1, characterized in that: In step 2, the mass ratio of the dried seaweed leaves to the activator is (1-4):(4-1).
8. The method for preparing a seaweed-derived alloy carbon sodium ion battery negative electrode material according to claim 5, characterized in that: The inert atmosphere includes a combination of one or more of helium, neon, argon, krypton, xenon, radon and nitrogen.
9. The method for preparing a seaweed-derived alloy carbon sodium ion battery negative electrode material according to claim 1, characterized in that: In step 2, the length of the chopped seaweed leaves is less than 0.5 mm.
10. The method for preparing a seaweed-derived alloy carbon sodium ion battery negative electrode material according to claim 1, characterized in that: In step 1, the seaweed blade is the blade portion remaining after the central rib of the seaweed is removed.